Incentives and Deterrents to the Supply of Long-term Care for the Elderly in England: Evidence and Experience in Two Local Authorities. Issue 2 (4th April 2022) - Allan, Stephen; Darton, Robin
Abstract : This article reports on a study assessing the incentives and deterrents to long-term care (LTC) supply in two local markets in England. The supply of LTC in many countries is facing the issues of rising demand, (lack of) workforce and the interaction of the public and private sectors. Findings from qualitative interviews of local council and provider stakeholders exploring barriers and enablers faced by LTC providers in two local authorities (LAs) are presented and discussed. The interviews provided insight in three main areas: staffing, demand and stakeholder relationships. Staffing, in particular, is crucial and we found that there are many difficulties for providers in maintaining their workforce. Consistent with previous research, we also found that public spending levels on LTC puts pressure on providers striving to maintain a good quality service, including improved remuneration of staff.